2011
DOI: 10.1021/am2002907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carboxylic Acid on Sintering of Inkjet-Printed Copper Nanoparticulate Films

Abstract: The reduction effect of various carboxylic acids on inkjet-printed copper film was investigated. Carboxylic acids were exposed to the film by nitrogen gas that was bubbled through the liquid acids during the annealing process. It was observed that in the case of saturated monocarboxylic acid (formic, acetic, propionic, butyric), the acids with shorter hydrocarbon chains perform better in reducing the surface copper oxides in the printed copper conductive film. The printed films exposed to formic acid vapor exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 19 publications
0
93
0
Order By: Relevance
“…26 The chemical transformation into phase-pure Cu nanowires through a simple wet treatment facilitated the fabrication of highly conductive Cu nanomaterials at room temperature without the incorporation of toxic chemical environments, unlike the previously reported methods. 27,28 Notably, for AgNWs prepared using sophisticated procedure, an annealing process at slightly elevated temperatures ranging from 80 − 220°C is highly recommended for inducing nano-welding between neighboring nanowires owing to the presence of organic capping molecules. In some cases, this can limit the integration of thermally vulnerable functional moieties.…”
Section: Resultsmentioning
confidence: 99%
“…26 The chemical transformation into phase-pure Cu nanowires through a simple wet treatment facilitated the fabrication of highly conductive Cu nanomaterials at room temperature without the incorporation of toxic chemical environments, unlike the previously reported methods. 27,28 Notably, for AgNWs prepared using sophisticated procedure, an annealing process at slightly elevated temperatures ranging from 80 − 220°C is highly recommended for inducing nano-welding between neighboring nanowires owing to the presence of organic capping molecules. In some cases, this can limit the integration of thermally vulnerable functional moieties.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the lactic acid can react with copper oxide/ hydroxide to form an organic copper salt, which is subsequently reduced into elemental copper at elevated temperatures under a protective atmosphere. 24,25 Therefore, as long as the resulting organic copper salt is soluble in a given solvent, lactic acid would be an effective chemical remover for both surface oxide/hydroxide. Lactic acid treatment leads to the formation of copper lactate as a result of the reaction with the copper oxide/hydroxide, as follows:…”
Section: Annealing-free Fabrication Y Won Et Almentioning
confidence: 99%
“…The problem is that an actual bonding surface consists of an oxide film and a machined layer; [3][4][5][6][7] therefore, adhesion between surfaces at the bond interface and removal of the oxide film represent necessary requirements to obtain high bond strength. Recently, ultrasonic vibration, [8][9][10][11][12][13] plasma processing, [14][15][16][17][18][19] and organic acid pretreatment [20][21][22][23] have been investigated as methods for breaking and cleaning a superficial oxide film. Indeed, in a previous study, we showed that modification of an oxide film with formic acid greatly improves the strength of bonding between tin surfaces 22) and between tin and copper.…”
Section: Introductionmentioning
confidence: 99%